(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
Never in the history of knowledge production in the age of Western-centred modernity has the idea of indigenous knowledges been as important to the imagination of the future of the world as in the 21st century. This is mainly because the 21st century is a period in which the current hegemonic Western ways of knowing, imagining and seeing the world have proved to be inefficient in providing solutions to many of the global challenges that they have caused. This failure by the Western knowledge production system to provide lasting solutions to the most pressing challenges of the 21st century that it has caused, such as the global financial crisis, conflict and climate change, has led to the emergence of the question of whether a different model of the world outside the Western-centred one can be imagined. This article is a decolonial critique of the popular but controversial subject of indigenous knowledges in the 21st century. The article argues that the idea of indigenous knowledges can serve as a basis on which another world outside the present Western-centric one can be imagined.